Sie sind auf Seite 1von 11

# Queen’s College

## Mock Examination 2005-2006

PURE MATHEMATICS, PAPER I
1.(a) (1  x ) n  C 0  C 1 x  C 2 x 2 ...  C n x n (1) 1A for (1)
Since Cr = Cn – r , (1  x )  C n  C n 1 x  ...  C 0 x
n n
(2)
Consider the derivative:
d d 1M for using differentiation
(1  x ) 2 n   (1  x ) n
(1  x ) n 
dx dx
d
2n (1  x ) 2 n 1  2(1  x ) n (1  x ) n
dx 1M for using product rule or chain
d rule
n (1  x ) 2 n 1   C n  C n 1 x  ...  C 0 x n   C 0  C1x  C 2 x 2 ...  C n x n 
dx
1A for correct result
n1  x    C1  2C 2 x  3C 3 x 2  ...  nC n x n 1   C n  C n 1 x  ...  C 0 x n 
2 n 1

(3)

(b) Comparing the coefficient of xn-2 on both sides of (3) in (a), 1M for comparing coefficient
1A for writing both sides
n ( 2 n  1)! correctly
C1 C 2  2C 2 C 3  3C 3 C 4  ...  ( n  1)C n 1 C n  n C n2 n 21 
( n  2)! ( n  1)!

## 2. a , b are the roots of x2 – x – 1 = 0, a > b

1A for Vieta’s theorem or
By Vieta’s theorem , a + b = 1, a b = – 1 ……(1)
a2  a 1 0
1
Let P(n) the proposition be : a n  a n
b n
 b2  b  1  0
5
1
For P(0), a0 = 0 = a 0  b0  . \ P(0) is true. 1A for P(0), P(1)
5
For P(1), L.H.S. = a1 = 1
1 1 1
R.H.S. =  a 1  b1    a  b  2  4ab  12  4( 1)  1 \
5 5 5
P(1) is true.
1A for inductive hypothesis
Assume P(k-1) and P(k) are true for some integer k, that is,
1 1
a k 1   a k 1  b k 1  , ak  a k  bk  ………(2)
5 5
1M for second principle
For P(k + 1), a k 1  a k  a k 1
1 1
 a k  bk    a k 1  b k 1  , by (2) 1A for using Vieta’s Theorem
5 5
1
  a k
 b k   1   a k 1  b k 1  ( 1) 
5

1
1 1A for deducing correctly
  a k
 b k   a  b    a k 1  b k 1  ab  , by (1)
5
1
  a k 1  b k 1  \ P(k + 1) is true.
5
By the Principle of Mathematical Induction, P(n) is true for all natural numbers, n.
3. (a) cos 5q + i sin 5q = (cos q + i sin q)5 1M for de Moivre’s Theorem
= cos q + 5 cos q (i sin q) + 10 cos q (i sin q) + 10 cos q (i sin q) +
5 4 3 2 2 3
1M for Binomial Theorem
5 cos q (i sin q)4 + (i sin q)5
= cos5 q - 10 cos3 q sin2 q + 5 cos q sin4 q 1A for correct expansion
+ i (5 cos4 q sin q - 10 cos2 q sin3 q + sin5 q)
By comparing real parts, 1M for sin2 q = 1 – cos2 q
cos 5q = cos5 q - 10 cos3 q sin2 q + 5 cos q sin4 q
= cos5 q - 10 cos3 q (1 – cos2 q) + 5 cos q (1 – cos2 q)2
= 16 cos 5 q  20 cos 3 q  5 cos q
(b) By setting cos 5q = cos q (16 cos4 q - 20 cos2q + 5) = 0
1A for roots of cos 5q = 0
 3 
The principal roots are  ,  ,
10 10 2
1M for deleting the extra root
 3
The principal roots of 16 cos q - 20 cos q + 5 = 0 are 
4 2
,  .
10 10
Let x = cos q , by comparion, the roots of 16x4 – 20 x2 + 5 = 0
 3
are  cos ,  cos 1A for answers
10 10

4. (a) x3 – 2x2 + 5x – 3 = 0
1A for all values correct
a+b+g=2
ab + bg +ga = 5 ….(1)
abg = 3
(b) a2 + b2 + g2 = (a + b + g)2 – 2(ab + bg +ga) 1M for completing square
= 2 – 2 (5) , by (1)
2

## (c) a , b and g be the roots of x3 – 2x2 + 5x – 3 = 0

a 3  2a 2  5a  3  0 …..(2)
1M for property of roots
b 3  2b 2  5b  3  0 …..(3)
g 3  2 g 2  5g  3  0 …..(4)
(2) + (3) + (4),   a  5 a   3  0
a3  2 2

##  a3  2  a2  5 a   3  2( 6)  5( 2)  3(3)  13

2
5. 1M for subtraction
x x2 a3  x3 R 2  R 2  R1 x x2 a3  x3
  b b2 a 3  b3  b  x ( b  x )( b  x ) ( x  b)( x 2  bx  b 2 )
c c2 a 3  c3 R 3  R 3  R1 cx (c  x )( c  x ) ( x  c)( x 2  cx  c 2 )

## x x2 a3  x3 1M for taking out factors

 ( b  x )(c  x ) 1 bx  ( x  bx  b )
2 2

1 cx  ( x 2  cx  c 2 )

x x2 a3  x3
R3  R3  R2
( b  x )( c  x ) 1 bx  ( x 2  bx  b 2 )

0 cb ( b  c) x  ( b  c)( b  c)

## x x2 a3  x3 1M for Sarrus Rule of expansion

 ( b  c)( x  b )( x  c) 1 bx  ( x  bx  b 2 )
2

0 1 xbc

##  ( b  c)( x  b)( x  c)[bx ( x  b  c)  (a 3  x 3 )  x ( x 2  bx  b 2 )] 1A for correct factorization

= (b – c)(b – x)(c – x)(bcx – a ) 3

a3 1A for roots
 0 x  b or x  c or x  , where bc ¹ 0
bc
1 1
6. (a) v k 1  v k  
( 2k  1)( 2 k  3) ( 2 k  1)( 2k  1)
1M for joining fractions
( 2k  1)  ( 2k  3)

( 2k  1)( 2k  1)( 2k  3)
4

( 2 k  1)(2 k  1)( 2 k  3)
2n 2n
1 1M for using v
(b) 
kn
uk  
4
 (v
kn
k 1  vk )

## 1 1 1 1  1M for difference method

  v 2 n 1  v n      
4 4  ( 4n  1)(4 n  3) ( 2 n  1)( 2n  1) 
1  ( 2 n  1)( 2 n  1)  ( 4 n  1)( 4 n  3) 
  
4  ( 4 n  1)( 4 n  3)( 2 n  1)( 2 n  1) 
1  12n 2  16n  4 
  
4  ( 4n  1)( 4n  3)( 2 n  1)( 2 n  1) 

## 3n 2  4 n  1 (3n  1)( n  1) 1A for answer

 
( 4 n  1)( 4 n  3)(2 n  1)(2 n  1) ( 4n  1)(4n  3)(2 n  1)(2 n  1)

3
7. 9x4 – 27x3 + 8x2 – 27x + 9 = 0
Divide the whole equation by x2, we have

 1   1
9 x 2  2   27 x    8  0 ….(1) 1M for dividing by x2
 x   x
1
1 1 1 for calculating x 2 
Let y  x  , then y 2  x 2   2, x2   y2  2 1A x2
x x2 x2
The equation (1) becomes:
9(y2 – 2) – 27 y + 8 = 0
9y2 – 27 y – 10 = 0
(3y – 10) (y + 1) = 0
1A for y
10 1
\ y or 
3 3

10 1 10
(i) When y  , x 
3 x 3
\ 3x – 10x + 3 = 0
2

\ (3x – 1)(x – 3) = 0
1
\ x or 3
3
1 1 1
(ii) When y   x 
3 x 3
\ 3x + x + 3 = 0
2

1 35i
\ x
6
1  1  35i
The four roots of the equations are x  , 3 and .
3 6

 cos  sin 
8. (a) (i) P 4 4
 sin  
 cos 
 4 4  1A for describing the angle of
 rotation
\ P is a matrix of rotation through an angle anticlockwisely.
4

4
 1 1 
  1A
8. (a) (ii) P  2
1 2
 1 1 
 
 2 2
 1 1   1 1 
  5  13    1A
P QP  
1 2 2   2
 2
 1 1   13 5  1 1 
   
 2 2  2 2 
 1 1 
  1A may be omitted if last answer
 2 2   4 2  9 2 
 1 1   4 2 9 2  is correct
 
 2 2
 8 0 
  1A
 0 18 
a b 1M for letting M
(b) (i) Let M    . Then
c d
x  ax  by 
 x y  M        x y      
 y  cx  dy  1A for the simplified matrix
= (ax + 2bxy +dy + ) = (0)
2 2
1A for 
\ a = 5, b = c = -13, d = 5 (since M is symetric) and  = 72
 5 13  1A for M
\ M=   = Q and  = 72
  13 5 

5
X 1  x  x
(b) (ii) Let    P   , the image of   under the rotation through an
Y  y  y
 x X
angle of  about the origin. \    P 
4  y Y
The image of (*) under the rotation is:

 5 13   X 
 X Y P  1   P   (72)  (0) since PT = P-1
  13 5  Y

 1 1   1 1 
  5  13    1A
 X Y  2 2   2
 2   (72)  (0)
 1 1   13 5  1 1 
   
 2 2  2 2 
1A
 8 0 
X Y   (72)  (0) , by (a)(ii)
 0 18 
\ -8X2 + 18Y2 + 72 = 0
1A
X2 Y2
 1
9 4
1A
\ The curve (*) is a hyperbola.

## 9. (a) Let f ( x )  x 3  15 x 2  71x  105

Since f(x) has alternating signs in the coefficients, the roots of f(x) = 0 are positive.
By rational zero theorem, he possible rational roots are 1, 3, 5, 7, 15, 21, 35, 105.
f(3) = 33 – 15(32) + 71(3) – 105 = 0
1M for factor theorem
By factor theroem, x – 3 is a factor of f(x).
By division, f(x) = (x – 3)(x2 – 12x + 35)
1A for factorization
= (x – 3)(x – 5)(x – 7)
1A for roots
The roots of f(x) = 0 are 3, 5, 7.

(b) (i) x 3  px 2  qx  r  0
1M for Vieta’s Theorem
S1  a 1  a 2  a 3 = -p (1)
a1a 2  a 2 a 3  a 3 a1  q (2)
a 1a 2 a 3  r (3)
1M for expansion
2 2 2
S 2  a 1  a 2  a 3  ( a 1  a 2  a 3 )  2( a 1 a 2  a 2 a 3  a 3 a 1 )
2

= (-S1)2 – 2q = S12 – 2q

\ p  S1 , q
1
S
1
2
 S2  (4)
2
(b) (ii) Denoting S the symmetric sum,
1A correct expansion of S1
S1   a 1  a 2  a 3  
3 3
a 1
3
a a
3 1 2  6a 1 a 2 a 3 (5)

6
1A correct expansion of S2
S1S 2   a 1  a 2  a 3  a 1a 2  a 2 a 3  a 3 a 1 
(6)
 a  a a 1
3
1 2
Note: may use the method as
Q.4 (c)
3
(5) – 3(6), S1  3S1S 2  2 a 1
3
 6a 1a 2 a 3  2S 3  6r , by (3)

1 3 1 1 1A+1A
r S1  S1S 2  S3 (7)
6 2 3 for values of , 
1 1
 ,  .
2 3

 x  y  z  15
 2
(c)  x  y  z  83
2 2

 x 3  y 3  z 3  495

Put x  a 1 , y  a 2 , z  a 3
1A for correct evaluation
From (4), (7) p  15, q  71, r  105
1M for forming equation
The cubic equation form by the roots is t 3  15t 2  71t  105  0 .
By (a), the roots are 3, 5, 7.
2A deduct 1A for
\ (x, y, z) = (3,5,7) or (3,7,5) or (5,7,3) or (5,7,3) or (7,3,5) or (7,5,3)
(x, y, z) = (3,5,7)

 a 1 1 1 
  1A for determinant
10. (a) A=  1 a 1 1  , |A| = 3a2 + a3 = a2 (a + 3).
 1 1 a  1

 2a  a 2 a a 
  1A for minor and cofactor
Min A =  a 2a  a 2
a  , Cof A =
 a a 2a  a 2  (may be omitted if adj A is

correct)
 2a  a 2 a a 
 a 2a  a a 
2

 a a 2a  a 2 

 2a  a 2 a a 
  1A for inverse
Adj A =   a 2a  a a 
2

 a a 2a  a 2 

a  2 1 1 
1 
Inverse of A =    1 a  2  1  , where a ¹ 0, -3.
A a (a  3) 
 1  1 a  2 

7
 (a  1) x  y  z  1 a 1 1 1  x   1 
     
(b) (i)  x  (a  1) y  z  b is equivalent to  1 a 1 1  y    b 
 x  y  (a  1) z  b 2  1 1 a  1 z   b 2 
 
When a ¹ 0, -3, inverse of A exists,
1M for writing in inverse form

1
1M for multiplication of matrices
 x a 1 1 1   1  a  2 1  1  1 
      1   
 y   1 a 1 1   b    1 a  2  1  b 
z  1 1 a  1  b 2  a (a  3)   1  1 a  2  b 2 
     

 a  2  b  b2 
1  
   1  ( a  2) b  b 
2
a (a  3)  2 
  1  b  ( a  2) b 

a  2  b  b2  1  ( a  2) b  b 2  1  b  ( a  2) b 2
x , y , z
a (a  3) a (a  3) a (a  3)

 x  y  z 1
 1A for reducing the system
(b) (ii) When a = 0, the system of equation becomes:  xyzb
x  y  z  b 2

1A for reducing more
When b = 1 , the system becomes x + y + z = 1
and has infinite number of solution: (x, y, z) = (1 – t1 – t2, t1, t2).
When b ¹ 1 , the system is inconsistent and has no solution.

 2 x  y  z  1
 1A for reducing the system
(b) (iii) When a = -3, the system of equation becomes:  x  2 y  z  b
x  y  2z  b 2

Adding the 3 equations, b2 + b +1 = 0.
1M for knowing no real solution
Since  = 12 – 4(1)(1) < 0. The quadratic equation has no real solution.
\ The system of equations is inconsistent and has no solution.

## 11. (a) f(x) = ln x – x + 1 , x > 0

1A+1M for correct derivative and
1
f ' (x)   1  0 when x  1. setting it to 0 to find x = 1
x
When 0 < x < 1, f’(x) > 0.
1M for first derivative test
When x > 1, f’(x) < 0
1M for max
\ f(x) attains its maximum value at x = 1.
1A for comparing f(x) and f(1)
\ f(x) £ f(1) = ln 1 – 1 + 1 = 0 " x > 0.
\ f(x) £ 0 " x > 0.

8
a 1  a 2  ....  a n
(b) Let A  .
n
Then for i = 1, 2, …, n,
1A for using (a)
a  a  a
f  i   ln  i   i  1 £ 0
A A A
a  a
ln i  £ i  1
A A
n n 1A for taking sum
a   ai 
i 1
ln  i  £
 A  i 1
   1
A 
n 1M for property of ln
 a a ....a  1 1
ln  1 2 n n
 A  £ A a
i 1
i n
A
( nA )  n  0

a 1 a 2 ....a n
£1 1A for correct result
An

\G  n
a 1 a 2 ....a n £ A
1M for proof
ai
The equality holds if  1, "i, 1 £ i £ n.
A
i.e. a1 = a2 = …. = an = A.
a 1  a 2  ....  a n
(c)  n a 1 a 2 ....a n 1A n
n for a
i 1
i
n

\ a i 1
i  n n a 1 a 2 ....a n ….(1)

1
Replace a i by in (1), we have 1A n
1
ai for a
i 1
n i
1 1
a
i 1
n n
a 1 a 2 ....a n
….(2)
i
1M for multiplication
 n
 n
1
(1) ´ (2), we get 

 a   ai n
2
….(3)
i 1 i 1 i  1M for ai = i

 n   n 1
Put ai = i in (3),  
 i  n
 i 1   i 1 i 
2 1M for Si

n ( n  1)  n 1 1 1 2n
2

 i1 i 

  n  1   ....  
2

2 n n 1

9
12. (a) (1 + z)2n + (1 – z)2n = 0
2n
1M for transposing term
1 z 
   1  cis 
1 z 
1M for using de Moirvre’s Th.
1 z 2 k  
 cis  cis q k , where k = 0, 1, 2, …, (2n – 1).
1 z 2n
1  z  (1  z ) cis q k
1A for change of subject
cos q k  i sin q k  1
\ z
cos q k  i sin q k  1

qk qk qk
1  2 sin 2  2i sin cos 1 1M for using half-angle formula
 2 2 2
qk qk qk
2 cos 2  1  2i sin cos 1
2 2 2
qk
 q q 
2 sin sin k  i cos k 
 2  2 2
q  q q 
2 cos k cos k  i sin k  1A for getting answers
2  2 2
qk ( 2k  1) 
 i tan  i tan , where k = 0, 1, 2, …, (2n – 1).
2 2
( 2k  1)   4n  ( 2k  1) 
Since  tan  tan 1M for rewriting answers
2 4n
 2 2n  ( k  1)  1 
 tan where k = 0, 1, …., n – 1.
4n
  2k  1  
Hence the roots are z  i tan  , where k = 0, 1, …., n – 1.
 4n 
  2k  1  
12. (b) By (a), z  i tan  are roots of (1 + z)2n + (1 – z)2n = 0
 4n 
1M for writing factors
n 1
  2k  1     2k  1  
 z  i tan
corresponding to roots
(1  z) 2 n  (1  z) 2 n  A  z  i tan 
k 0 4n 4n 1A for writing the leading coeff.

2 ( 2 k  1)  
n 1
 2

1M for finding the leading coeff.
A  z  tan
k 0  4n 
Equating the coefficient z2n on both sides, we get A = 2.

2 ( 2k  1)  
n 1
 2
(1  z)  (1  z)  2
2n 2n
 
k 0 
z  tan
4n 

10
2 ( 2 k  1)  
n 1
 2
12. (c) (1  z )  (1  z)  2
2n 2n
 
k 0 
z  tan
4n 
….(1)
1M for using combination

( 2n )( 2n  1)
Coefficient of z2n – 2 on L.H.S. = C 22 n  C 22 n ( 1) 2  2 ´ 1A for correct coeff.
2
= 4n2 – 2n
1A for correct coeff.
n 1
( 2 k  1) 
Coefficient of z 2n – 2
on R.H.S. =2 
k 0
tan 2
4n
n 1
( 2k  1) 
2  sec
k 0
2

4n

 1

1M for changing to sec

n 1
( 2k  1) 
2  sec
k 0
2

4n
 2n

## Equating Coefficient of z2n – 2 on both sides,

n 1
( 2k  1) 
2  sec
k 0
2

4n
 2n  4n 2  2 n